The Role of Banking in Supporting Regional Development Economies (Literature Review) - Endah Suci Damayanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of the study is to provide an overview with a literature review of scientific articles related to variables and will be given an answer according to the perspective of the researcher in this scientific article and also to make a reference to science and knowledge, especially in regional development, banking, and other related sciences. The research method used is a literature review derived from existing scientific articles from various journals in the world related to variables. The research result that is related to variables and can be used as an additional reference for novelty or giving rise to a phenomenon. The researcher concluded there are three according to the discussion of the first research methods and objects of scientific articles, secondly the perspective of the reference researcher exists and this is only a small part, the three results of scientific articles have been compiled and given perspective by researchers in this scientific article.